TROIKA‐1: A double‐blind, randomized, parallel group, study aimed to demonstrate the equivalent pharmacokinetic profile of HD201, a potential biosimilar candidate to trastuzumab, versus EU‐Herceptin® and US‐Herceptin® in healthy male subjects. Issue 4 (26th July 2021) - Demarchi, Martin; Coliat, Pierre; Mclendon, Kristi; Chung Shii Hii, Jocelyn; Feyaerts, Peggy; Ang, Felicia; Jaison, Litha; Deforce, Filip; Derde, Marie Paule; Kim, Michael Jinwoo; Park, Lisa Soyeon; Detappe, Alexandre; et al.
Abstract: Prestige Biopharma Ltd (Singapore) has developed HD201, a proposed biosimilar to reference product trastuzumab. As a part of the stepwise approach to ensure comparability between the biosimilar candidate and the reference medicinal product, a phase I study in healthy subjects was conducted to demonstrate the pharmacokinetic (PK) equivalence (NCT03776240). The primary objective of the study was to demonstrate (PK) equivalence of HD201, EU‐Herceptin ®, and US‐Herceptin ® given at 6 mg/kg as a 90‐min i.v. infusion to healthy male subjects. A pairwise comparisons based on the primary endpoint AUC0–inf and secondary PK endpoints, AUC0–last and C max were undertaken. PK equivalence was to be concluded if the 90% confidence interval (CI) for the ratio of geometric means for each criterion were within the equivalence margin of 80% to 125%. Secondary objectives included assessment of other PK parameters, safety, tolerability, and immunogenicity in the three arms. A total of 105 healthy male subjects (35/treatment) were randomized in this study. The 90% CI for the ratios of AUC0–inf, C max and AUC0–last, were within 80%–125% for the comparisons of HD201 to EU‐Herceptin ® or US‐Herceptin ® and EU‐Herceptin ® to US‐Herceptin ® . The frequency of subjects with TEAEs of special interest was slightly lower in the HD201 group (20.0%) compared to the other treatment groups (EU‐Herceptin ® : 34.3%; US‐Herceptin ® : 31.4%). Only 1 subject (EU‐Herceptin ® group) developed anti‐drug antibodies prior to dosing. Overall, HD201 demonstrates PK similarity to both EU‐Herceptin ® and US‐Herceptin ® . The three study drugs also demonstrated similar safety profiles. Abstract : TROIKA‐1: A Double‐blind, Randomized, Parallel Group, Study aimed to demonstrate the equivalent pharmacokinetic profile of HD201, a potential biosimilar candidate to trastuzumab, versus EU‐Herceptin® and US‐Herceptin® in Healthy Male Subjects.